The Effect of Work-Family Conflict on Social Support for Career Women in The Special Region of Yogyakarta - Lita Chartika Febriyati; Annisa Warastri (Jurnal Indonesia Sosial Teknologi, 2024)
This study aims to analyze the influence of work-family conflict on social support received by career women in Yogyakarta. Work-family conflict is a condition in which the demands of work and family conflict with each other, thus causing stress for individuals. In the context of career women, these conflicts often cause stress and affect their psychological well-being. Social support is considered a factor that can help reduce the negative impact of work-family conflict. This study uses a quantitative approach with a survey method. Data was collected through a questionnaire distributed to 100 career women respondents working in Yogyakarta. This study uses a quantitative method. The results of the analysis showed that there was a significant negative relationship between work-family conflict and social support. The higher the level of work-family conflict, the lower the perceived social support. In addition, the study also found that support from family and co-workers has an important role in helping career women overcome conflicts between work and family. These findings highlight the importance of social support in improving the well-being of career women and reducing the negative impact of work-family conflict. The implications of this study are expected to be a reference for companies and organizations in designing policies that support work-life balance for female employees